The value of the local wisdom of Karma phala in the practice of accountability of the traditional system of the village of Tenganan Pegurinsingan - Dharmawan, Nyoman Ari Surya; Hariadi, Bambang; Adib, Noval (The International Journal of Accounting and Business Society, 2023)
Objective – This study wants to uncover the value of local wisdom behind the accountability practices implemented by the Balinese Customary Institutions. Design-Method—This type of research is qualitative and uses an ethnomethodological approach. This approach is chosen to explore research problems by understanding the daily life of the subject being studied. Findings—This study found that accountability practices applied to Indigenous institutions are certainly based on phala karma. Karma phala is rooted in two words: karma, which means "deed" or "action," and phala, which means "fruit" or "result." Karma phala means "the fruit of deeds," both what has been done and what will be done. Originality—Praktik accountability and karma phala are two uncertain concepts that cannot be separated if they are connected with responsibility, deeds, and rewards.  Research Implications – This study found that honesty and fear of karma phala led members in Indigenous institutions to work honestly and transparently to create accountability that family because of the customary customs of the people who uphold the existing and applicable awig-awig